Productive Zakat Viewed From The Perspective of Modern Fiqh - Syamsuar (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
Zakat in Islamic teaching has two perspectives,'worship of mahdah and social empowerment. According to some ulemas, zakat has upgraded the standard of the people's life. In the 'Umar ibn Abd al-'Aziz era, zakat was formatted as a capital for the poorman. The case of empowering the ummah became the important issue let alone many of them live in unlucky conditions. What 'Umar ibn Abd al-'Aziz has done is considered as productive zakat. Nowadays, zakat is usually distributed for consumer importance. If the end model cannot upgrade the condition of the ummah, then productive zakat is considered a solution to solve the problem.